(Additional Effects of Chitosan and Turmric Solution to Soup Noodle Quality) - Alamsyah, Rizal; Susanti, Irma; Nurhayati, Lilis (Warta Industri Hasil Pertanian, 2008)
Soup noodle is one kind of the noodle that prevered by a lot of Indonesian people. Sunch noodle has short shelf life due to easiness for deterioration. The prolong the shelf life of this noodle, chemical ingredients are commonly used as formalin solution taht is harmful for humankind health. There are some alternatives of natural preservatities such chitosan and turmeric that can be treated to substitute the chemical preservatities. This study was devoted to investigate the effect of natural preservatives chitosan and turmeric sollution addition on soup noodle quality. The experiments use soup noodle which immerses into: 15ppm, 45ppm and 75 ppm of chitosan solution. 1% and 1.5% of turmeric solution. The analysis of quality of soup noodle were conducted in term of visual deterorietion, pH, moinsture content, totalized titration acid, total plate count (TPC), and opganoleptic tests. The experiment showed that soup noodle which were immersed into 15 ppm, 45 ppm, and 75 ppm of chitosan solution as well as into 1% and 1.5% of tumeric solution keep noodle good only for less then 24 hours. The soup noodle in the next 24 hours has a bad smell, acid condition, and TFC value is not eligible to the SNI standard that 1.0 x 10-6 coloni/g.